The perspective of capability providers in creating a sustainable I4.0 environment. Issue 8 (7th July 2020) - Lardo, Alessandra; Mancini, Daniela; Paoloni, Niccolò; Russo, Giuseppe
Abstract : Purpose: With the increasing pressures towards global sustainability and the transition to Industry 4.0 (I4.0), the collaboration between firms and other key stakeholders is essential. Value is no longer created by firms acting autonomously, but rather by firms acting together with external parties. Therefore, the aim of this study is to explore the potential contribution of capability providers to a Sustainable I4.0 Environment as an additional perspective regarding the management decisions of a smart and sustainable business model (SSBM) transformation of big corporations. Design/methodology/approach: An in-depth qualitative case study of Futuryng INC., which is a company based in Silicon Valley, New York and Italy, is presented and analysed through interviews, secondary sources and using a triangulation approach. The company is a Connected Technologies Ecosystem, which acts as a provider of technology building blocks (capability) able to design and release end-to-end Information Technologies–Internet of Things–Operational Technologies (IT-IoT-OT) Solutions. Findings: From the case study, the authors determine that the success of big corporations' SSBM transformation requires a Sustainable I4.0 Environment approach where capability providers play a relevant role and act as enablers. Then, the authors develop a framework by adopting an actor perspective, called the Sustainable I4.0 Environment, highlighting the contribution of the capability provider in the sustainable I4.0 business model transformation of a big corporation. Practical implications: The authors' analysis clarifies that the successful execution of a sustainable I4.0 business model transformation requires integrated thinking for management decisions and a co-creation approach with capability providers, along with an open innovation process. Originality/value: In the analysis of I4.0 and sustainability issues, previous studies only focus on implementing firms and view the environment merely as a background in which act forces of sustainability and I4.0. A comprehensive overview of the Sustainable I4.0 Environment, which considers actors and their contribution, is lacking. By integrating the literature review with the case study, the authors' research proposes a comprehensive framework to guide the decision process of transformation from a traditional business model (TBM) to an SSBM and considers one of the key actors involved, the capability providers.